The determinant factors of efficiency on Islamic banking and conventional banking in Indonesia - Nur Majdina; Jono M. Munandar; Jaenal Effendi (University of Merdeka Malang, 2019)
As intermediary institutions, conventional banks have larger amount of loans to third party funds than of Sharia banks. Thus, the bank needs a performance appraisal to measure banking operations through efficiency. We examine the efficiency of Islamic banks and conventional banks in Indonesia and analyzes the factors that influence the level of efficiency known as the Two-Stage Data Envelopment Analysis method. We found that there are significant efficiency differences between Islamic banking and conventional banking in the 1st quarter 2014- 4th quarter 2017. On the other hand, NPF and NPL results affected negatively towards Islamic and conventional banks efficiency. Asset and CAR affected positively significant toward Islamic banks efficiency. Asset and ROA had affected positively significantly toward conventional banks efficiency but CAR had affected positively insignificantly toward conventional banks. Lastly, ROA had affected positively insignificantly toward Islamic banks efficiency.JEL Classification: G31, G32, G33DOI: https://doi.org/10.26905/jkdp.v23i3.3157